Female fertility treatment and adverse birth outcomes: a multistate analysis of pregnancy risk assessment monitoring system data. (30th December 2022) - Uribe, Danielle; Haak, Peterson; Nechuta, Sarah
Abstract: Objective: The popularity of fertility treatments has continued to rise, however, the potential health risks of these treatments for both mother and infant are not fully known. Our objective was to determine the association between fertility treatments and adverse birth outcomes of intended pregnancies using the Pregnancy Risk Assessment Monitoring System (PRAMS) data. Methods: Data from 27, 018 intended pregnancies, collected from 2009 to 2018 in the United States, were included in our analysis. PRAMS data consisted of questionnaire and birth certificate data. SAS 9.4 was used for analyses accounting for complex survey weights. All analyses were conducted separately for singleton and twin births. Weighted percentages with 95% confidence intervals (CIs) were estimated for maternal characteristics and birth outcomes. Multivariable logistic regression was used to determine adjusted odds ratios (OR) and 95% CIs for associations of fertility treatment use and adverse birth outcomes. Results: Close to 12% of women reported the use of any fertility treatment. Among those using fertility treatments, the most common type was assisted reproductive technology (ART) for both twin (68.7%, 95% CI: 62.3, 75.2) and singleton births (45.1%, 95% CI: 42.0, 48.1). Use of any type of fertility treatment for singleton births was associated with increased odds of a cesarean delivery (OR: 1.31, 95% CI: 1.16, 1.47), preterm birth (OR: 1.42, 95% CI: 1.20, 1.67), a small-for-gestational age infant (OR: 1.20, 95% CI: 1.00, 1.44), and an infant hospital stay >5 days (OR: 1.34, 95% CI: 1.11, 1.62). Use of fertility treatment for twin births was associated with cesarean delivery only. In analyses examining associations for specific types of treatment (medication alone, ART, insemination) with birth outcomes, results varied by treatment type. Conclusions: In this large population-based sample of women who intended to become pregnant and had a live birth, fertility treatment was associated with adverse birth outcomes. Patients seeking fertility treatment should be appropriately counseled on the risks of adverse maternal and infant birth outcomes overall and by treatment type. Maternal support and resources to prevent adverse birth outcomes among women using fertility treatments are warranted.